A reconfigurable crosslinking system via an asymmetric metal–ligand coordination strategy. Issue 17 (13th April 2022) - An, Xiaoming; Li, Yiran; Xu, Ming; Xu, Zhicheng; Ma, Wencan; Du, Ruichun; Wan, Gang; Yan, Hongping; Cao, Yi; Ma, Ding; Zhang, Qiuhong; Jia, Xudong
Abstract : We report an asymmetric metal–ligand coordination strategy for reconfigurable elastomers. EXAFS is first introduced to monitor the structure change in M–L crosslinked polymers during stretching at the molecular level. Abstract : Metal–ligand (M–L) coordination crosslinked elastomers have shown potential in multiple fields. However, innovative molecular designs and profound characterizations into the short-range structure remain a challenge. Here, we report an asymmetric M–L coordination strategy as a new design for polymers. Through a one-pot multi-component polymerization, a primary thio-β-diketone was introduced into the polymer chain, based on which a series of metal-coordination crosslinked elastomers were prepared. Compared with the symmetric ligand, the primary thio-β-diketone showed higher binding ability and dynamics, resulting in higher mechanical strength and lower hysteresis. Isothermal titration calorimetry, single-molecule force spectroscopy and rheology measurements were applied to prove the consistency between different scales for the coordinating elastomers. Benefitting from the simple and unique coordinating system, extended X-ray absorption fine structure (EXAFS) was exploited to survey the change of coordinating structures during stretching, observing the extension, distortion and breaking of coordination bonds directly. This strategy can pave the way for new designs of metal–ligand interactions in material science.